(untitled) (Baghdad Science Journal, 2025)
An antibacterial and antifungal piperonal-derived compound and its Rh(III), Pd(II), Pt(IV), and Cd(II) metal complexes were synthesized and characterized by spectroscopic methods, conductivity, metal analyses and magnetic moment measurements. The nature of the complexes formed in ethanolic solution was studied following the molar ratio method. From the spectral studies, octahedral geometry was suggested for rhodium (III) and platinum (IV) complexes, while a square planer structure was suggested for palladium (II) complex and a tetrahedral geometry for cadmium (II) complex. Structural geometries of these compounds were also suggested in gas phase by using hyperchem-8 program for the molecular mechanics and semi-empirical calculations. The heat of formation and binding energy for the prepared compounds was calculated by using PM3 and AMBER methods. The theoretically vibration spectra for the imine and its starting material was evaluated by using PM3 method. Preliminary in vitro tests for antibacterial and antifungal activity showed that most of the prepared compounds display a good activity to (Staphylococcus aureus), (Escherichia coli) and (Candida albicans).